Continuous purification and culture of rat type 1 and type 2 alveolar epithelial cells by magnetic cell sorting - Di Liu; Jian-Hui Sun; Hua-Cai Zhang; Jian-Xin Jiang; Ling Zeng (Chinese Journal of Traumatology, 2022)
Purpose: The incidence of acute lung injury (ALI) in severe trauma patients is 48% and the mortality rate following acute respiratory distress syndrome evolved from ALI is up to 68.5%. Alveolar epithelial type 1 cells (AEC1s) and type 2 cells (AEC2s) are the key cells in the repair of injured lungs as well as fetal lung development. Therefore, the purification and culture of AEC1s and AEC2s play an important role in the research of repair and regeneration of lung tissue. Methods: Sprague-Dawley rats (3–4 weeks, 120–150 g) were purchased for experiment. Dispase and DNase I were jointly used to digest lung tissue to obtain a single-cell suspension of whole lung cells, and then magnetic bead cell sorting was performed to isolate T1α positive cells as AEC1s from the single-cell suspension by using polyclonal rabbit anti-T1a (a specific AEC1s membrane protein) antibodies combined with anti-rabbit IgG microbeads. Afterwards, alveolar epithelial cell membrane marker protein EpCAM was designed as a key label to sort AEC2s from the remaining T1α-neg cells by another positive immunomagnetic selection using monoclonal mouse anti-EpCAM antibodies and anti-mouse IgG microbeads. Cell purity was identified by immunofluorescence staining and flow cytometry. Results: The purity of AEC1s and AEC2s was 88.3% ± 3.8% and 92.6% ± 2.7%, respectively. The cell growth was observed as follows: AEC1s stretched within the 12–16 h, but the cells proliferated slowly; while AEC2s began to stretch after 24 h and proliferated rapidly from the 2nd day and began to differentiate after 3 days. Conclusion: AEC1s and AEC2s sorted by this method have high purity and good viability. Therefore, our method provides a new approach for the isolation and culture of AEC1s and AEC2s as well as a new strategy for the research of lung repair and regeneration.